2021
DOI: 10.3390/rs13040553
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sentinel-1 Multi-Configuration and Multi-Temporal Series for Monitoring Parameters of Winter Wheat

Abstract: The present study aims to investigate the potential of multi-configuration Sentinel-1 (S-1) synthetic aperture radar (SAR) images for characterizing four wheat parameters: total fresh mass (TFM), total dry mass (TDM), plant heights (He), and water content (WC). Because they are almost independent on the weather conditions, we have chosen to use only SAR. Samples of wheat parameters were collected over seven fields (three irrigated and four rainfed fields) in Southwestern France. We first analyzed the temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The backscattering coefficient values are sensitive to the soil moisture and the water vegetation content [49][50][51]. Based on this assumption, the backscattering coefficient information of Sentinel-1 was used in [52] to estimate the water stress index.…”
Section: Estimation Of the Water Stress Coefficient Ksmentioning
confidence: 99%
“…The backscattering coefficient values are sensitive to the soil moisture and the water vegetation content [49][50][51]. Based on this assumption, the backscattering coefficient information of Sentinel-1 was used in [52] to estimate the water stress index.…”
Section: Estimation Of the Water Stress Coefficient Ksmentioning
confidence: 99%
“…The result is in contrast with Nasirzadehdizaji et al (2019), where VH-VV (R 2 =0.63) has slightly better correlation with PH compared to VH+VV (R 2 =0.61). Gorrab et al (2021) found that cumulative VH+VV improved estimation on PH to (R 2 =0.89). Compared to VH-VV, VH+VV contributed the least or none to SD, AGDB and LNC estimation models.…”
Section: Variable Importance Of Best Performing Modelsmentioning
confidence: 92%
“…However, all these studies have used a relatively small study area and only involved single or few orbit passes images which can bypass the backscatter bias due to incidence angle difference and geometry effects (Arias et al, 2022). Gorrab et al, (2021) reported that no impact of using 2 orbit passes and incidence angles in estimating winter wheat vegetation variables in their experiment. Their experiment also compared VV, VH, VH+VV, and VH-VV backscatter with cumulative values and found out that the cumulative backscatter of VH+VV best estimated wheat height (R 2 =0.89) and total dry mass (R 2 =0.74).…”
Section: Introductionmentioning
confidence: 99%
“…σ 0 VH , σ 0 VV , σ 0 VH-VV and RVI, and three optical RSI, i.e NDVI, fCover and GAI, have been considered. As an alternative of raw RSI, we proposed new indicators (noted RSI ) based on the cumulative sum of each RSI, and already successfully applied to the estimation of wheat parameters [47]:…”
Section: ) Definition Of Remote Sensing Indicators (Rsi)mentioning
confidence: 99%